Cronistas coloniales. (Biblioteca Ecuatoriana Mínima. La Colonia y la República, 1960)
Contine:Francisco de Jerez, Pedro Sancho de la Hoz, Pedro Pizarro, Pedro Gutiérrez de Santa Clara,Ddiego Fernandez llamado el Palentino,Juan Cristobal Calvete de Estrella, Nicolas de Albenino, Pedro Cieza de León, Agustín de Zarate,Antonio de Herrera l. Tordesillas